Investigation of Quality of Propolis Acquired in Minas Gerais - Marcucci, Maria Cristina [UNESP]; Melo, Adriana; Carneiro, Mara Junqueira; Rosa, Paulo Cesar Pires (Sociedade Brasileira de Quimica (SBQ), 2024)
Propolis is a resin produced by bees from buds and exudates of plant sources. Its use is increasing exponentially, especially after reports of its use as an adjuvant in the therapy against COVID-19. In this scenery, many products can be found on the market, which do not have the minimum quality characteristics established by government agencies, and the most serious, some of them are true frauds, inducing the consumer to use something that is nothing more than a panacea. The objective of this work was to evaluate the physicochemical characteristics of four propolis extracts, the antimicrobial and antioxidant activity, in order to observe frauds practiced in MG. Qualitative and quantitative tests, the HPLC profile, the antioxidant and antimicrobial activities were performed. Samples 1 to 3 showed several non-conformities in relation to what is recommended in the Brazilian Legislation, a fact that is reflected in the weak antioxidant and antimicrobial activity. Sample 4 presented all compliant results. The chemometrics analysis showed the separation of propolis, highlighting the difference between true (4) and false samples. This work showed the evident fraud in bee products offered on the market, especially propolis, and alerted a greater inspection by the government agencies.
Investigação da Qualidade da Própolis Adquirida em Minas Gerais
Keywords: adulteration; antibacterial activity; antioxidant activity; Propolis; quality control